Motherhood confined: maternal health in English prisons, 1853-1955 - Bennett, Rachel E. (Social histories of medicine, 2024)
The book is the first extensive historical examination of motherhood in English prisons. It addresses the challenges mothers and babies have historically posed to prison systems not designed with their containment and the management of their health in mind